Grain sterility in relation to dry mass production and distribution in rice (Oryza sativa L.) - Puteh, Adam; Mondal, Md Monjurul Alam; Ismail, Mohd Razi; Latif, Mohammad Abdul (Hindawi Publishing Corporation, 2014)
The experiment was conducted to investigate potential causes of grain sterility in widely cultivated rice variety in Malaysia, MR219 and its two mutant lines (RM311 and RM109) by examining the source-sink relations. RM311 produced increased dry matter yield both at heading and maturity and also showed higher grain yield with greater proportion of grain sterility than the other two genotypes (RM109 and MR219) resulting in the lowest harvest index (49.68%). In contrast, harvest index was greater in RM109 (53.34%) and MR219 (52.76%) with less grain sterility percentage than MR311 indicating that dry matter partitioning to economic yield was better in RM109 and MR219 than in MR311. Results indicated that dry matter allocation per spikelet from heading to maturity was important for reducing grain sterility in rice. The greater above-ground crop dry matter per spikelet was observed in RM109 and MR219 as compared to high dry matter producing genotype; RM311 implies that poor grain filling may not have resulted from dry matter production or source limitation. These findings suggest that grain sterility or poor grain filling in rice is the result of poor translocation and partitioning of assimilates into grains (sink) rather than of limited biomass production or source limitation.